Factors that Predispose Youth to Risk in Mexico and Chile - Cunningham, Wendy (2012)
About half of Latin America s youth are considered "at risk," meaning that they engage in or are at risk of engaging in risky behaviors that are detrimental to their own development and to the well-being of their societies. While child psychologists identify many factors that may cause some youth to engage in at-risk behaviors and others not to, only empirical evidence can identify the set that is relevant to a particular population. This paper uses youth surveys from Chile and Mexico to test which of a large set of potential factors are correlated with a range of risky behaviors among youth. These factors range from relationships with parents and institutions to household behaviors (abuse, discipline techniques) to social exclusion. The authors use stepwise regressions to sort out which variables best explain the observed variance in seven different risky behaviors. They find that higher socioeconomic status, a good relationship with parents and peers, strong connection with local governmental institutions and schools, urban residence, younger age, and spirituality emerge as key explanatory factors for all seven behaviors for boys and girls in both countries. This points to a wider range of policy entry points than currently used, including targeting parents and the relationship with schools.